Navigating Chronic Disease Management with Digital Healthcare Solutions amidst the COVID-19 Pandemic: A Systematic Literature Review - Vratimos, Achillefs; Champilomatis, Ilias; Farantos, Georgios (European Scientific Journal, ESJ, 2025)
The purpose of this paper is to critically evaluate data collected from various studies on Chronic Disease Management during the COVID-19 pandemic and the emergence of Digital Healthcare as a means of providing innovative approaches for the management of chronic diseases.A systematic literature review was conducted based on studies found in the Pubmed database, wihle the search included studies with no publication date time limit, given that COVID–19 emerged in 2019. A Prisma diagram was created to record the way and the criteria by which we included and excluded studies for our research. Out of the 567 records identified through various sources 85 were used for a qualitative synthesis.During the first wave of the pandemic, a significant reduction or complete cancellation of scheduled health appointments was observed. At the beginning of the COVID-19 pandemic, shortages of medication used to manage chronic conditions were also recorded due to global supply chain disruptions. Since the beginning, governments acted rapidly to promote the use of teleconsultations by introducing enabling legislation and revising laws ensuring continuity of care for people with chronic diseases, thus transitioning rapidly to remote care and monitoring.The use of telemedicine and the involvement of community pharmacists for the management of chronic patients are key factors for sustained adherence. Long-term policies are vital to prevent pandemic-driven health disparities, while lessons should be derived for future preparedness, managing subsequent waves, and ensuring testing in primary care.